ANALISIS KEBUTUHAN MAHASISWA TERHADAP KEBERADAAN LAYANAN BIMBINGAN KONSELING - Giyono (Jurnal Evaluasi dan Pembelajaran, 2019)
Problem research is student difeculte in problem solving This Research was aimed at descritively students needs the are park guidance and counseling service in FKIP Lampung Univercity. The gools research for understanding student’ needs in mendapatkan assistance service in problem solving for study. The methods gathering data use questionaire and anallysis data whit descriptitive analytic. The subjects were 345 student’ of FKIP Lampung Univercity. The results of this research is (1) The student very nececere are park guidance and counseling service on FKIP Lampung University (2) Academic guidance not yet optimal to given assistence in problem solving. Keywords: Needs, Services, Guidance and Counseling